RFID-enabled parking system for enhanced accessibility of disabled drivers - Shamrudin, Muhammad Amrin; M. Zin, Nor Affida; Mohd. Atan, Fadila; Sidik, Norbaiti (School of Mechanical Engineering, 2025)
In today's fast-paced technological landscape, Radio Frequency Identification (RFID) technology emerges as a transformative solution, utilizing wireless signals to uniquely identify objects, animals, or individuals. However, the persistent challenges faced by disabled individuals in accessing essential services, particularly within parking facilities, underscore the urgent need for innovative solutions. Traditional parking setups often lack accommodations for disabled drivers, creating barriers to their mobility and independence. This proposal advocates the integration of RFID technology into parking infrastructure, establishing dedicated parking spots equipped with RFID sensors. These sensors would enable real-time identification and reservation of accessible spaces, streamlining the parking experience for disabled drivers. Beyond enhancing accessibility, the implementation of an RFID-based parking system holds the potential to optimize parking management efficiency and foster inclusivity in urban environments. Through collaborative efforts between technology developers, policymakers, and disability advocacy groups, this initiative aims to empower disabled individuals, ensuring their equal participation in community life while promoting independence and inclusivity.